Norwid’s Tears. On Lyricism and Rhetoric - Seweryn, Agata (Colloquia Litteraria, 2018)
The text presents in a multi-faceted way the motif of tears in Norwid’s writings. The motif is shown within a new research context, i.e. the tradition of baroque rhetoric. The author proposes a well-supported thesis, in which she argues that in the case of Norwid’s writings lyricism grows out of the rhetoric thus creating a new artistic dimension.